The local employment impacts of mining : an econometric analysis of job multipliers in northern Sweden - Moritz, Thomas; Ejdemo, Thomas; Söderholm, Patrik; Wårell, Linda (Mineral Economics, 2017)
The way in which mining contributes to job opportunities in the region where it takes place has become increasingly important for the industry’s relations to the local community. The employment impacts of mining are however far from straightforward to assess. Considering these uncertainties about real-life job impacts, it is vital that there are sound assessments of these employment effects. The purpose of this paper is to apply a novel econometric approach to assess mining-induced job multipliers in the empirical context of northern Sweden. This analysis employs data on the number of employees in selected non-mining sectors and in the mining sector, respectively, and covering the relatively recent mining boom period (2003-2013). We also highlight differences across the two main mining counties in northern Sweden. The results show a positive statistical relationship between increases in the number of employees in the mining sector and changes in the number of employees in other sectors. The private services sector is particularly affected, while the industrial sector also benefits in the specific case of mining municipalities. The results also indicate relatively large inter-county differences, in turn highlighting the importance of addressing the context-specific circumstances when estimating the employment effects of mining. Validerad; 2017; Nivå 1; 2017-03-23 (rokbeg)